The impact of weather changes on air quality and health in the United States in 1994–2012 - Iny Jhun; Brent A Coull; Joel Schwartz; Bryan Hubbell; Petros Koutrakis (Environmental Research Letters, 2015)
Air quality is heavily influenced by weather conditions. In this study, we assessed the impact of long-term weather changes on air quality and health in the US during 1994–2012. We quantified past weather-related increases, or ‘weather penalty’, in ozone (O _3 ) and fine particulate matter (PM _2.5 ), and thereafter estimated the associated excess deaths. Using statistical regression methods, we derived the weather penalty as the additional increases in air pollution relative to trends assuming constant weather conditions (i.e., weather-adjusted trends). During our study period, temperature increased and wind speed decreased in most US regions. Nationally, weather-related 8 h max O _3 increases were 0.18 ppb per year (95% CI: 0.06, 0.31) in the warm season (May–October) and 0.07 ppb per year (95% CI: 0.02, 0.13) in the cold season (November–April). The weather penalties on O _3 were relatively larger than PM _2.5 weather penalties, which were 0.056 μ g m ^−3 per year (95% CI: 0.016, 0.096) in warm months and 0.027 μ g m ^−3 per year (95% CI: 0.010, 0.043) in cold months. Weather penalties on O _3 and PM _2.5 were associated with 290 (95% CI: 80, 510) and 770 (95% CI: 190, 1350) excess annual deaths, respectively. Over a 19-year period, this amounts to 20 300 excess deaths (5600 from O _3 , 14 700 from PM _2.5 ) attributable to the weather penalty on air quality.